2011
DOI: 10.1371/journal.pone.0015723
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Activation and Differentiation Signals Regulate Schlafen-4 Gene Expression: Evidence for Schlafen-4 as a Modulator of Myelopoiesis

Abstract: BackgroundThe ten mouse and six human members of the Schlafen (Slfn) gene family all contain an AAA domain. Little is known of their function, but previous studies suggest roles in immune cell development. In this report, we assessed Slfn regulation and function in macrophages, which are key cellular regulators of innate immunity.Methodology/Principal FindingsMultiple members of the Slfn family were up-regulated in mouse bone marrow-derived macrophages (BMM) by the Toll-like Receptor (TLR)4 agonist lipopolysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 42 publications
6
78
0
Order By: Relevance
“…Since we showed that the deletion of Ctcf does not significantly affect the expression levels of TLR4, TLR8 and TLR9 mRNA, and since these genes are not direct targets of Ctcf, the observed effect may have been indirectly caused through type I IFN. 42 Regulation of TNF expression by Ctcf is in agreement with the literature. 43 Additionally, we show diminished IL-10 production by macrophages as a result of Ctcf depletion, similarly to low IL-10 production upon Ctcf deletion in Th2 cells as we previously observed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Since we showed that the deletion of Ctcf does not significantly affect the expression levels of TLR4, TLR8 and TLR9 mRNA, and since these genes are not direct targets of Ctcf, the observed effect may have been indirectly caused through type I IFN. 42 Regulation of TNF expression by Ctcf is in agreement with the literature. 43 Additionally, we show diminished IL-10 production by macrophages as a result of Ctcf depletion, similarly to low IL-10 production upon Ctcf deletion in Th2 cells as we previously observed.…”
Section: Discussionsupporting
confidence: 89%
“…A set of genes downregulated during macrophage differentiation but induced upon TLR stimulation are the Schlafen (Slfn) genes, especially Slfn4. 42 In our data set, the expression levels of Slfn1, Slfn4 and Slfn9 genes were lower after LPS stimulation in LysM-Cre Ctcf f/f than in control macrophages (ratio: 0.21, 0.38 and 0.38, respectively). Since we showed that the deletion of Ctcf does not significantly affect the expression levels of TLR4, TLR8 and TLR9 mRNA, and since these genes are not direct targets of Ctcf, the observed effect may have been indirectly caused through type I IFN.…”
Section: Discussionmentioning
confidence: 61%
“…Several mouse Slfn genes, including Slfn1 (4), Slfn 2 (9), and Slfn3 (13, 14, 16) have been shown to play key regula- tory roles in control of cell proliferation and/or differentiation. Mouse Slfn2 has been implicated in immune cell quiescence (10), whereas Slfn4 has been implicated in the control of myelopoiesis (17).…”
Section: Discussionmentioning
confidence: 99%
“…The only evidence for regulatory effects of Slfn3 on cell growth stems from prior work, in which ectopic expression of this Slfn member in human colon cancer cells inhibited cellular growth (16). The function of Slfn4 is not well known at this time, as there is only one report showing its involvement in macrophage activation and differentiation (17). Similarly, the functions of the remaining members of the Slfn family are largely unknown.…”
Section: There Is Emerging Evidence That the Ifn-inducible Family Ofmentioning
confidence: 99%
“…Her mother (I:2) had a platelet count in whole blood of 83 × 10 9 /l, with a less severe bleeding history. The platelet count in patient cell-cycle regulation, proliferation, and differentiation (10)(11)(12)(13)(14). Recently, data have been published suggesting an important function for SLFN14 as an endoribonuclease, regulating rRNA and ribosome-associated mRNA cleavage and translational control in rabbit reticulocytes (15).…”
Section: 12mentioning
confidence: 99%